Comparison of selected established body fat percentage prediction equations among female preadolescents / Annis Mahat - Mahat, Annis (2013)
The purpose of this study were to compare between the selected established prediction equations of body fat percentage with BIA among female preadolescents aged 10-12 years old. There were fifteen selected existing body fat percentage equations derived from the Asian population including two equations derived based on Caucasian and African American equation (Slaughter equation). In total, 60 females preadolescents whose mean±SD age, height, weight and BMI were 10.80years±0.78, 1.40m±0.08, 35.88kg±l 1.83 and 18.1 lkgm_2±4.76, respectively. Body composition were measured by using skinfold technique and BIA. This study found that there was a significant difference between the selected existing body fat percentages predictions equations in children except for the E9 and El 0 equations (both were Tahara’s equations, 2002). The E9 equations were under- and over estimated (3.2% and 8.7%) and the E10 equations were under- and overestimated (4.6% and 8.2%) in %BF female preadolescent. In conclusion, there was a good agreement between the two %BF value which were E7 (Nagamine & Suzuki, 1964 equation) with BIA and it indicates the E7 equation can be used widely to measure body composition in female preadolescents.